Active twist of model rotor blades with D‐spar design - Kovalovs, Andrejs; Barkanov, Evgeny; Gluhihs, Sergejs (Transport, 2007)
The design methodology based on the planning of experiments and response surface technique has been developed for an optimum placement of Macro Fiber Composite (MFC) actuators in the helicopter rotor blades. The baseline helicopter rotor blade consists of D‐spar made of UD GFRP, skin made of +450/‐450 GFRP, foam core, MFC actuators placement on the skin and balance weight. 3D finite element model of the rotor blade has been built by ANSYS, where the rotor blade skin and spar “moustaches” are modeled by the linear layered structural shell elements SHELL99, and the spar and foam ‐ by 3D 20‐node structural solid elements SOLID 186. The thermal analyses of 3D finite element model have been developed to investigate an active twist of the helicopter rotor blade. Strain analogy between piezoelectric strains and thermally induced strains is used to model piezoelectric effects. The optimisation results have been obtained for design solutions, connected with the application of active materials, and checked by the finite element calculations.First Published Online: 27 Oct 2010